Prevalence of herbal medicine use by UK patients/consumers: a systematic review of surveys. Issue 1 (18th February 2013) - Posadzki, Paul; Watson, Leala K; Alotaibi, Amani; Ernst, Edzard
Abstract Objective To estimate the prevalence of herbal medicine (HM) use in the UK. Methods The databases AMED, CINAHL, COCHRANE, EMBASE and MEDLINE were searched for peer‐reviewed surveys published between January 2000 and September 2011. The authors' own departmental files were also manually searched for relevant references. Results Ten surveys were included with a total of 20 601 participants. All surveys had major methodological limitations. Across all surveys, the average prevalence rate for a range of time periods was 37.1% (range 4.8–92.4). One‐year prevalence was provided by just one survey and amounted to 36%. The vast majority of patients did not discuss their use of HM with a conventional healthcare professional. The average incidence rate of adverse effects that was associated with HM use was 15.8%. Conclusion Many UK patients and/or consumers use HM, often without consulting their conventional healthcare professionals. In order to maximise patient‐safety, a full medical history should include questions about HM usage.